Research progress on the pharmacological effects of Poria cocos: a narrative update - Guo, Yanquan; Liu, Tianyuan; Li, Dan (Frontiers in Nutrition, 2026)
Poria cocos, a traditional medicinal and food homologous herb, has various therapeutic effects, including promoting urination, dispersing dampness, strengthening the spleen, and calming the mind. Its core active ingredients mainly consist of polysaccharides and triterpenoids. Recent studies have shown that Poria cocos and its active components play a crucial regulatory role in various physiological and pathological processes. It demonstrates a wide range of pharmacological activities, including renal protection, improving digestive system function, enhancing sleep quality, immune regulation, antioxidant effects, anticancer properties, and the modulation of glucose-lipid metabolism. These mechanisms involve multifaceted regulation of gut microbiota and glycolipid metabolism. This review systematically summarizes the latest research progress on the chemical composition and pharmacological effects of Poria cocos over the past 3 years (2023–2025), aiming to provide a scientific basis for its further development and clinical application.